1995
DOI: 10.1073/pnas.92.21.9495
|View full text |Cite
|
Sign up to set email alerts
|

A nerve growth factor peptide retards seizure development and inhibits neuronal sprouting in a rat model of epilepsy.

Abstract: Kindling, an animal model of epilepsy wherein seizures are induced by subcortical electrical stimulation, results in the upregulation of neurotrophin mRNA and protein in the adult rat forebrain and causes mossy fiber sprouting in the hippocampus. Intraventricular infusion of a synthetic peptide mimic of a nerve growth factor domain that interferes with the binding of neurotrophins to their receptors resulted in significant retardation of kindling and inhibition of mossy fiber sprouting. These rmdings suggest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(16 citation statements)
references
References 39 publications
1
14
0
1
Order By: Relevance
“…Our findings that NGF administration accelerates kindling rates and enhances mossy fiber sprouting are compatible with those of Van der Zee et al (1995) and Rashid et al (1995), who demonstrated that intraventricular infusion of NGF inhibitors retards kindling rates and reduces mossy fiber sprouting. Taken together, these findings indicate that NGF plays an important role in regulating the development of kindling and kindling-induced neural growth.…”
Section: Potential Mechanism For Increased Kindling Rates and Enhancesupporting
confidence: 81%
“…Our findings that NGF administration accelerates kindling rates and enhances mossy fiber sprouting are compatible with those of Van der Zee et al (1995) and Rashid et al (1995), who demonstrated that intraventricular infusion of NGF inhibitors retards kindling rates and reduces mossy fiber sprouting. Taken together, these findings indicate that NGF plays an important role in regulating the development of kindling and kindling-induced neural growth.…”
Section: Potential Mechanism For Increased Kindling Rates and Enhancesupporting
confidence: 81%
“…These abnormal connections may be responsible for the development of chronic hyperexcitability in the hippocampus and for chronic seizures (Sutula et al 1988;Davenport et al 1990;Houser et al 1990;Meberg et al 1993b;Bendotti et al 1994;Elmer et al 1996). The trigger for this abnormal axonal plasticity could be the death of some hilar neurons and the trophic stimulation of granule cells after seizures (Holtzman and Lowenstein 1995;Rashid et al 1995). As discussed above, loss of hilar neurons and increased trophic factor expression also occurs in granule cells after ischemia, but the present studies in rat indicated only moderate increases in expression of GAP-43 in granule cells.…”
Section: Discussionmentioning
confidence: 96%
“…We recently developed a highly potent small peptide that allosterically inhibits TrkB signaling in neurons and that is active in vivo after systemic delivery (20). Our in vivo study, together with others' studies (21)(22)(23), demonstrates the feasibility of developing heterocyclic ligands that can modulate TrkB activity in living animals. However, peptide-derived ligands have the problem of being proteolytically unstable, which potentially decreases their efficiency under therapeutic conditions.…”
Section: Introductionmentioning
confidence: 97%